2004
DOI: 10.1529/biophysj.103.037200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanomolar Concentrations of Sodium Dodecyl Sulfate, a Catalytic Inductor of α-Helices, on Human Calcitonin Incorporation and Channel Formation in Planar Lipid Membranes

Abstract: Human Calcitonin (hCt) is a peptide hormone which has a regulatory action in calcium-phosphorus metabolism. It is currently used as a therapeutic tool in bone pathologies such as osteoporosis and Paget's disease. However, due to its amphiphilic property tends to form a gelatinous solution in water which consists of fibrils that limits its therapeutic use. Here we show that sodium dodecyl sulfate (SDS), an anionic detergent able to induce and stabilize alpha-helices in polypeptides, at a monomeric concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 83 publications
(102 reference statements)
2
19
0
Order By: Relevance
“…The responses observed during successive stimulations up to the 7 th one resulted quantitatively undistinguishable from those evoked by the first one (data not shown) as evidenced qualitatively in Figure 2D showing that no significant long-term effects occurred. In agreement with previous reports, [49][50][51][52][53] this survey of SDS on exocytosis confirmed that 250-350 μM corresponded to an adequate concentration range for our purpose in this study. Yet, to ensure the absence of any non-obvious long-term effects, only the spikes delivered during the first 10 s range after the first stimulation were treated quantitatively.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The responses observed during successive stimulations up to the 7 th one resulted quantitatively undistinguishable from those evoked by the first one (data not shown) as evidenced qualitatively in Figure 2D showing that no significant long-term effects occurred. In agreement with previous reports, [49][50][51][52][53] this survey of SDS on exocytosis confirmed that 250-350 μM corresponded to an adequate concentration range for our purpose in this study. Yet, to ensure the absence of any non-obvious long-term effects, only the spikes delivered during the first 10 s range after the first stimulation were treated quantitatively.…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, SDS is reported to stabilize the transient nanopores that constantly form in cellular membranes 38 or contribute to the formation of trans-membrane channels. 49,50 Hence, Ca 2+ intake is expected to occur spontaneously after brief SDS stimulation, thus initiating exocytosis by triggering the physiological Ca 2+ -induced cascade recalled above. 9 Therefore, to validate the physiological relevance of the results presented and discussed hereafter it was essential to firstly assess if this is effectively the case when exocytosis is elicited by SDS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BOG, DPC and DHPC). In addition, SDS was reported to induce α-helical structure formation in the peptide of a membrane protein at SDS:peptide 1:1000 molar [44] and was proposed to be a "catalytic inducer" of α-helices. The mechanism of how SDS folds apolipoproteins into helix requires further investigation.…”
Section: Interaction With Lipid Mimicking Detergentsmentioning
confidence: 99%